PLAY AND ITS SIGNIFICANCE IN CORECTIVE GYMNASTICS FOR PRE-SCHOOL CHILDREN - Grujo Bjeković; Vesna Bratovčić; Đorđe Arnaut (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
In present life conditions, especially in urban environment, children have very poor conditions for physical activities, or for movement in general. According to the new researches, working conditions and quality of work in nurseries and schools, especially if they are related to physical exercises, have certain influences on overall development of pre-school and school children. Childhood is ideal time for correction of numerous postural disturbances and deformities, whether they are congenital or acquired by injury, wrong body posture, or by poor nutrition. Playing is a power fultool for directing correct development of children, so very of ten it has to be adapted to age, capabilities, interests and needs of children.